Rash Impulsiveness and Negative Mood, but not Alexithymia or Reward Sensitivity, Differentiate Young to Middle-Aged Chronic Daily Smokers from Never-Smokers. Issue 1 (1st January 2018) - Lyvers, Michael; Bremner, Monique; Edwards, Mark S.; Thorberg, Fred Arne
ABSTRACT: Given the well-established associations of the personality traits alexithymia, impulsivity, and reward sensitivity with problematic use of a variety of substances, including alcohol and cannabis, the present study sought to determine whether daily tobacco smoking is similarly linked to these traits. Male and female adults aged 18 to 40 years were recruited from the local Australian community, allowing comparison of demographically similar samples of current daily smokers ( n  = 47) to never-smokers ( n  = 59) on the relevant self-report measures. Multivariate analysis of covariance revealed that current smokers scored significantly higher than never-smokers on indices of negative mood, impulsiveness, and risky alcohol use, after controlling for social desirability. No significant group differences were found on indices of alexithymia, reward sensitivity, or punishment sensitivity. Results suggest that chronic daily cigarette smoking may be an exception to the maladaptive behaviors associated with alexithymia, and is driven primarily by mood regulation and poor impulse control.